A systematic review of approaches for testing concurrent programs. (10th December 2015) - Arora, Vinay; Bhatia, Rajesh; Singh, Maninder
Summary: Concurrent programs are replacing the sequential programs as they utilize the true capabilities of multicore architecture. The extensive use of multicore systems and multithreaded paradigms warrants more attention to the testing of the concurrent programs. The testing concurrent program is not a new field as it has been more than 40 years because the first problem related to the testing concurrent program was addressed by the researchers. The field covers various domains, which include concurrency problems, testing approaches, techniques, graphical representations, tools, and subject systems. This paper aims at providing an overview of research in the domain of testing concurrent programs by classifying it into eight categories: (a) reachability testing, (b) structural testing, (c) model‐based testing, (d) mutation‐based testing, (e) slicing‐based testing, (f) formal methods, (g) random testing, and (h) search‐based testing. The survey is focused on the techniques applied, methodologies followed, and tools used in these aforementioned approaches. Furthermore, the gaps are also identified in different approaches. The paper concludes with the consolidation of various testing parameters along with the future directions. Copyright © 2015 John Wiley & Sons, Ltd.